Improving the Performance of Health Polytechnic Employees of the Ministry of Health, RI Jambi, Based on Discipline - Azizah Azizah; Evi Adriani; Dwi Putri Budiningtyas (International Journal of Multidisciplinary Sciences and Arts, 2024)
The aim of this research is to foster work discipline to improve employee quality, an organization will achieve optimal results in carrying out its work. The method used in this research is quantitative with literature studies, studies carried out using literature that is closely related to the research object, which is intended to obtain learning. The sample from this research was 43 employees of the General Department and Program Development Division at the Indonesian Ministry of Health's Health Polytechnic in Jambi. The data analysis technique used is simple linear regression analysis using the SPSS (Statistical Package For Social Science) program. Based on the results of the regression analysis, the regression equation Y = 8.448 + 0.928 .7% while 33.3% was influenced by other variables not examined in this research. Partially, the discipline of the employees of the Republic of Indonesia Ministry of Health's Health Polytechnic in Jambi. There is a significant influence between discipline on employee performance at the Indonesian Ministry of Health's Health Polytechnic in Jambi, namely tcount 9.165 > ttable 2.01954, seen from the significance level of ?=0.05 so 0.000 is smaller than 0.05. So the decision is that H0 is rejected and Ha is accepted. The conclusion of this research is that good performance will come from hard work and high discipline.